The Use of Orthostatic Device for 90 Minutes Does Not Change Cardiovascular and Biomechanical Parameters of Patients with Spinal Cord Injury - Liana Praça Oliveira; Reginaldo Florencio da Silva; Marie Aquino Melo de Leopoldino; Sarah Carvalho Frota; Gabriella Coelho Vieira de Melo Alves; Jefferson Pacheco Amaral Fortes; Pedro Henrique Gomes Muniz; Gisele Harumi Hotta; Francisco Carlos de Mattos Brito Oliveira; Francisco Fleury Uchoa Santos-Júnior (Applied Bionics and Biomechanics, 2022)
Background. Changes in autonomic function are often caused by spinal cord injuries, which lead to limited orthostatic positioning in these patients. Objective. To investigate the cardiovascular and biomechanical parameters during 90 min of postural elevation equipment usage comparing spinal cord injury and healthy subjects. Methods. A device was used that allowed patients with spinal cord injuries to remain in an orthostatic posture for 90 min. During this period, the physiological parameters were measured every 15 min. Cardiovascular parameters (heart rate, oxygen saturation, blood pressure, and autonomic nervous system) and biomechanical parameters of the plantar pressure distribution were evaluated. For blood pressure, heart rate, oxygen saturation, and autonomic nervous system, a two-way analysis of variance was applied. The mixed-effect model was applied to plantar pressure. The significance level was set at p<0.05 for all statistical analyses. Results. No differences were observed between the groups in systolic blood pressure (F=0.07), diastolic blood pressure (F=0.14), heart rate (F=0.56), and oxygen saturation (F=0.23) at any of the time intervals throughout the experiment (p>0.05). No statistical difference was observed in the mean plantar pressure values between the groups (p=0.35) during the period in which they remained in the orthostatic position. Conclusion. The present study showed the absence of differences between spinal cord injury patients and control participants using the orthostatic device in terms of cardiovascular and biomechanical parameters over 90 min.